PENGUATAN KADER KESEHATAN DALAM DETEKSI DINI PENYAKIT TIDAK MENULAR - Lumastari Ajeng Wijayanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus continue to experience increasing prevalence and often go undetected until serious complications occur. Health cadres have a crucial role as the frontline in early screening in the community, but are often hampered by limited technical skills and outdated knowledge. This community service activity aims to increase the capacity and independence of health cadres in conducting early detection of NCDs through intensive training and technical assistance. The implementation of the activity used the Participatory Action Research (PAR) method in the first stage (education). Data analysis used the Wilcoxon Signed-Rank Test statistical test on 235 respondents. Based on the results, the movement in the level of knowledge of cadres before and after the provision of education was obtained. The Ranks table shows that there were 110 respondents (46.8%) who experienced an increase in knowledge (Positive Ranks), 125 respondents (53.2%) had a constant level of knowledge (Ties), and none of the respondents (0%) experienced a decrease in knowledge (Negative Ranks). There is a significant difference in the level of knowledge of cadres before and after the intervention. Providing education has proven to be significantly effective in increasing cadre knowledge. ABSTRAK Penyakit Tidak Menular (PTM) seperti hipertensi dan diabetes melitus terus mengalami peningkatan prevalensi dan sering kali tidak terdeteksi hingga terjadi komplikasi serius. Kader kesehatan memiliki peran krusial sebagai garda terdepan dalam skrining awal di masyarakat, namun sering kali terkendala oleh keterbatasan keterampilan teknis dan pengetahuan yang belum terbarui. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas dan kemandirian kader kesehatan dalam melakukan deteksi dini PTM melalui pelatihan intensif dan pendampingan teknis. Pelaksanaan kegiatan menggunakan metode Participatory Action Research (PAR) pada tahap pertama (edukasi). Analisis data menggunakan uji statistik Wilcoxon Signed-Rank Test terhadap 235 responden, Berdasarkan hasil didapatkan pergerakan tingkat pengetahuan kader sebelum dan sesudah pemberian edukasi. Tabel Ranks menunjukkan terdapat 110 responden (46,8%) yang mengalami peningkatan pengetahuan ( Positive Ranks ), 125 responden (53,2%) memiliki tingkat pengetahuan yang tetap ( Ties ), dan tidak ada satupun responden (0%) yang mengalami penurunan pengetahuan ( Negative Ranks ). terdapat perbedaan yang bermakna pada tingkat pengetahuan kader sebelum dan sesudah diberikan intervensi. Pemberian edukasi terbukti efektif secara signifikan dalam meningkatkan pengetahuan kader..